CAN DENTURE STOMATITIS BE TREATED WITH ORGANIC INGREDIENTS ?-mini review - Dana Gabriela Budală; Maria Bolat; Roxana Ionela Vasluianu; Dan Nicolae Bosînceanu; Carina Balcoș; Zinovia Surlari; Monica Mihaela Scutariu; Florinel Cosmin Bida; Dragoș Ioan Virvescu; Elena Raluca Baciu (Romanian Society of Oral Rehabilitation, 2022)
Introduction: Behavioral management approaches are employed with youngsters who are scared or unwilling to cooperate. Podiatric patients' discomfort and anxiety can be alleviated by the use of pharmacologic sedation, anesthesia, and analgesia. Oral sedative midazolam is frequently prescribed for children because of its safety, rapid onset, and mild amnesia, all of which make it a popular choice among pediatricians. Midazolam/ketamine and its combinations are discussed in this review article, covering the advantages of using oral route of sedation, pharmacokinetics and range of oral dosages, and the use of antagonists for clinical dentistry treatment procedures.